Pengenalan Simbol dalam Kemasan Obat pada Masyarakat di Area Car Free Day Jakarta - Susanto, Sharon; Christian, Yulius Evan; Susanto, Michael Darell; Putri, Fadhilla Sivana; Nababan, Agnes Aditia; Gunawan, Untung (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Symbols on drug packaging are vital for providing essential information regarding the usage, dosage, and safety warnings of medications. A lack of understanding of these symbols may lead to improper use of drugs, posing potential health risks. This community service initiative aimed to increase public awareness of these symbols through socialization activities targeted at the visitors of Car Free Day (CFD) Jakarta, a popular public gathering space with diverse individuals. The objective of this initiative was to evaluate the level of public understanding before and after the socialization of the symbols on drug packaging. A total of 60 participants were engaged in identifying the symbols on drug packaging, followed by an educational session explaining the meanings of these symbols. Data was collected using questionnaires and analyzed to determine whether there was a notable improvement in participants' understanding. The results indicated a significant increase in public knowledge following the educational intervention. The findings suggest that socialization efforts on the understanding of packaging symbols can enhance public awareness, potentially leading to safer and more informed medication use. It is recommended that similar socialization activities be conducted in other areas with high foot traffic to expand the reach of this educational effort.